Putative Androgen Exposure and Sexual Orientation: Cross-Cultural Evidence Suggesting a Modified Neurohormonal Theory. (1st December 2015) - Ellis, Lee; Lykins, Amy; Hoskin, Anthony; Ratnasingam, Malini
ABSTRACT: Introduction: According to neurohormonal theory, prenatal androgens are key determinants of sexual orientation. As a reputed marker for prenatal androgens, the 2D:4D finger length ratio has been used in more than a dozen studies to test the hypothesis that prenatal androgens influence sexual orientation. Findings have been very inconsistent. Aim: The present study sought to retest the hypothesis that 2D:4D and sexual orientation are related is a manner consistent with neurohormonal theory. Methods: A 2D:4D measure (of the right hand) along with four additional somatic markers of androgen exposure (height, physical strength, muscularity, and athletic ability) with samples of college students in Malaysia (N = 2, 058) and the United States (N = 2, 511). The five androgen measures were factor analyzed, resulting in a two-factor solution: Factor 1 consisted of strength, muscularity, and athletic ability (the muscular coordination factor ), and Factor 2 was comprised of the r2D:4D and adult height (the bone growth factor ). Main Outcome Measures: Sexual orientation was measured by asking each respondent the extent to which they were sexually attracted to males and the extent to which they were sexually attracted to females, both on 11-point scales. Results: When the countries and sexes were analyzed separately, neither the r2D:4D measure nor Factor 2 correlated with sexual orientation to significant degrees. Instead, it was the muscular coordination factor that correlated the best. Support was found for the hypothesis that prenatal androgens influence sexual orientation, but the nature of these influences was more complex than neurohormonal theory predicted. Conclusion: A modified theory is needed and presented to accommodate the results from this study.